Seroprevalence of Toxoplasma gondii and Neospora caninum infections and associated factors in sheep from Costa Rica - Villagra-Blanco, Rodolfo (Parasite Epidemiol Control, 2019)
The presence of antibodies against Toxoplasma gondii and Neospora caninum were analyzed in 392 sheep sera from ten Costa Rican ovine flocks using indirect immuno-enzymatic assays. Additionally, general information about sheep management, environment, and clinical reproductive disorders was assessed through a questionnaire to inquire factors related to these apicomplexan parasites. A total of 161 (41.1%) serum samples reacted positive to T. gondii, 43 (10.9%) to N. caninum and 26 (6.63%) to both parasites. Toxoplasma gondii serorreactors were detected in all the analyzed flocks (100.0%), meanwhile N. caninum antibodies were found in nine flocks (90%), from the six Costa Rican regions. Factors associated with T. gondii were the co-presence of cattle (OR = 5.06; C.I.95%; 2.08–12.30; p: <0.001), grey foxes (Urocyon cinereoargenteus) and opossums (Didelphis marsupialis) (OR = 2.44; C.I.95%; 1.50–3.95; p: <0.001) inside or around the farms, and the presence of peccaries (Tayassu sp.) (OR = 0.35; C.I.95%; 0.16–0.74; p: 0.0058) was a variable associated with N. caninum seropositivity. The obtained results of T. gondii and N. caninum infections in sheep flocks from Costa Rica should be considered for the proper prevention and control strategies against these apicomplexan abortive parasites.